Morphological And Molecular Identifications Of Aspergillus Spp. Isolated From Enclosed Buildings In Peninsular Malaysia - Rahman, Wardah Abdul (2012)

(untitled)
Aspergillus is frequently found and easily spread in almost any type of environments. The potentially pathogenic, allergenic and toxigenic of Aspergillus have been reported previously. As most individuals spent more than 80% of their time indoors, the occurrence of Aspergillus in indoor environment is crucial to human health. Moreover, bioaerosols which also consists of Aspergillus spores could be one of the main factors in controlling a good Indoor Air Quality (IAQ). In Malaysia, reports on the occurrence of Aspergillus in indoor environments are still limited and rarely reported.